Recent advances and future prospects of electrochemical processes for microalgae harvesting - Nageshwari, Krishnamoorthy; Unpaprom, Yuwalee; Ramaraj, Rameshprabu; Gaanty Pragas, Maniam; Govindan, Natanamurugaraj; Arunachalam, Thirugnanam; Balasubramanian, Paramasivan (Elsevier Ltd, 2021)
Over the years, algae have found wide scope of utility in a variety of environmentally beneficial processes like biofuel production, removal of heavy metals from wastewater sources for potential bioremediation, monitoring water pollution and source of animal nutrition. However, the conventional harvesting methods pose a set-back in terms of energy, cost and operational complications due to the small size of microalgae. Of all the processes, harvesting alone corresponds to approximately 30% of the total production costs. Recent advancements in the microalgal technology have brought many efficient techniques into use for improved recovery of microalgae. This review comprehends the development, principle, influencing parameters and directions to future research of one of the state-of-the-art approaches for harvesting microalgae, electrochemical technology. Though this area was previously explored for its application in wastewater treatment, it has lately gained momentum in the field of microalgae due to its economic efficiency. This paper highlights the three prime processes used to yield microalgae namely electroflocculation, electroflotation and a combined electrocoagulation-flotation (ECF) system. Several encroachments and strategies among these techniques have also been elucidated. The review focusses on the effect of most significant process controlling parameters such as reactor and electrode design, various surface properties of microalgae, current, pH, salinity and agitation that influence harvesting. In addition, the economy and energy aspects that emphasize the welfares of this technology over others have been extensively discussed. The overall work aims to provide an insight into the electrochemical methods, their challenges and opportunities that might be beneficial for carrying out further research and scope for industrial applications.